HUBUNGAN RIDING CONDITION, RIDING PERSONALITY DAN VEHICLE CONDITION TERHADAP SAFETY RIDING MAHASISWA PROGRAM STUDI S1 KESEHATAN MASYARAKAT - Makomulamin Makomulamin; Nila Puspita Sari (Al Tamimi Kesmas: Jurnal Ilmu Kesehatan Masyarakat (Journal of Public Health Sciences), 2020)
One of the modes of transportation used by students in their daily activities is two-wheeled vehicles (motorized). From the observations in the field, there are still many students who do not understand properly how to drive a survivor or safety Riding. As a result there are many accidents caused by negligence of the motorcyclist himself, committing traffic violations such as not turning on the sein, riding a motorcycle at high speed, flocking with more than one passenger and not wearing a helmet. This shows that there is still a lack of understanding and knowledge of students towards riding safety.The purpose of this study is to know the relationship between Riding Condition, Riding Personality and Vehicle Condition to Safety Riding. The type of research used in this research is observational with a quantitative analytical approach with cross sectional research design. The population was studied as many as 914 students with a sample of 90 people. The sampling techniques used are in a simple random way. Data analysis using chi-square statistical test with degree of meaning (α)=0.05. Research shows that variables that have a relationship with Safety Riding are Riding Personality (p value = 0.015), vehicle Condition (p value 0.006). It is expected that students to behave safely (safety riding) on the road when driving a vehicle, students can become Role Mode in improving knowledge, as well as concern for driving safety to avoid traffic accidents. Such as bad behavior smoking while driving, talking, using a mobile phone while driving, and violating traffic signs in driving